Targeting group II PAKs in cancer and metastasis. - Eswaran, J; Soundararajan, M; Knapp, S (2009)
The p21 activated kinases (PAKs) play an essential role in cell signaling and control a variety of cellular functions including cell motility, survival, angiogenesis and mitosis. PAKs are important regulators in growth factor signaling, cytoskeletal reorganization and growth factor-mediated cell migration. Overexpression of PAKs has been detected in many cancers and linked to increased migration potential, anchorage independent growth and metastasis. Six isoforms of PAKs are expressed in human and based on their regulatory properties they have been classified into group I (PAK1-3) and group II (PAK4-6). Besides the well studied group I family, members of the group II PAKs also emerged as interesting targets for the development of new inhibitors for cancer therapy. The availability of high resolution crystal structures for all group II PAKs and their fundamentally different regulatory properties when compared with group I enzymes has opened new opportunities for rational drug designing strategies. In this review, we summarize the results of recent advances of the function of group II PAKs in tumorigenesis and metastasis as well as opportunities for exploring the unique catalytic domain dynamics of this protein family for the design of group II PAK specific inhibitors.